2016
DOI: 10.1007/s10689-016-9917-1
|View full text |Cite
|
Sign up to set email alerts
|

First description of mutational analysis of MLH1, MSH2 and MSH6 in Algerian families with suspected Lynch syndrome

Abstract: Hereditary non-polyposis colorectal cancer (HNPCC) is an autosomal dominant disorder characterized by the early onset of colorectal cancer (CRC) linked to germline defects in Mismatch Repair (MMR) genes. We present here, the first molecular study of the correlation between CRC and mutations occurring in these genes performed in twenty-one unrelated Algerian families. The presence of germline mutations in MMR genes, MLH1, MSH2 and MSH6 genes was tested by sequencing all exons plus adjacent intronic sequences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
0
6
1
Order By: Relevance
“…In addition, a team in our lab have identi ed in a LS family with discordant twins, an MSH2 pathogenic mutation (c.1552C > T;p.Q518X) previously reported only in a Portuguese LS family and shared with all investigated family members suggesting that this variant is a causal mutation [28]. Furthermore, an Algerian recent study have reported the MSH2 (c.728G > A) mutation in two cases (44 and 38 years old) with CCR belonging to the same family [61]. MSH2 (c.728G > A) variant seems to be identi ed only in Mediterranean countries.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, a team in our lab have identi ed in a LS family with discordant twins, an MSH2 pathogenic mutation (c.1552C > T;p.Q518X) previously reported only in a Portuguese LS family and shared with all investigated family members suggesting that this variant is a causal mutation [28]. Furthermore, an Algerian recent study have reported the MSH2 (c.728G > A) mutation in two cases (44 and 38 years old) with CCR belonging to the same family [61]. MSH2 (c.728G > A) variant seems to be identi ed only in Mediterranean countries.…”
Section: Discussionmentioning
confidence: 79%
“…The hallmark of the syndrome is the presence of microsatellite instability (MSI) in the tumor. Several studies from the Middle East reported Lynch syndrome families, and the clinical features of Lynch syndrome families appear to be similar to those seen in Western families [ 4 ].…”
Section: What Proportion Of Crc In the Middle East Is Familial Or Hermentioning
confidence: 99%
“…In addition, a team in our lab have identified in a LS family with discordant twins, an MSH2 pathogenic mutation (c.1552C>T;p.Q518X) previously reported only in a Portuguese LS family and shared with all investigated family members suggesting that this variant is a causal mutation [ 29 ]. In addition, an Algerian recent study have screened MLH1 , MSH2 and MSH6 genes among 21 families from East of Algeria and have identified the MSH2 (c.728G>A) mutation in two cases (44 and 38 years old) with CCR belonging to the same family with colon cancer family history [ 62 ]. The MSH2 (c.728G>A) variant seems to be identified only in Mediterranean countries.…”
Section: Discussionmentioning
confidence: 99%